2017
DOI: 10.1039/c6ra27065d
|View full text |Cite
|
Sign up to set email alerts
|

Molecular design of advanced lubricant base fluids: hydrocarbon-mimicking ionic liquids

Abstract: This paper describes the molecular design and tribological evaluation of novel room-temperature ionic liquid (RTIL) lubricants, abbreviated as P-SiSOs. The RTILs are designed to mimic hydrocarbons, in order to ensure their compatibility with existing tribosystems as well as enable use of conventional additives.Steel-on-steel ball-on-flat reciprocating tribotests performed under atmospheric conditions show that the neat P-SiSOs exhibit favorable performances, resulting in friction and wear significantly lower t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 32 publications
3
11
0
Order By: Relevance
“…The inset figures (also found in SI) display the wear scars of the balls lubricated with neat P-SiSO, reference PFPE, and P-SiSO + PNA + OPP, which was the additive combination that produced the lowest coefficient of friction. By comparing the wear scars, it was also clear that all P-SiSO samples performed significantly better than the reference PFPE fluid in terms of wear, which was in line with our previous results using similar RTILs [24]. Although the additives appear to influence the wear scar morphology (as seen from the change in wear scar light reflection in Figure 7c), it was difficult to quantify the change in tribological performance in terms of wear with high accuracy.…”
Section: Stage 2: Effect Of Additives In P-sisosupporting
confidence: 59%
See 1 more Smart Citation
“…The inset figures (also found in SI) display the wear scars of the balls lubricated with neat P-SiSO, reference PFPE, and P-SiSO + PNA + OPP, which was the additive combination that produced the lowest coefficient of friction. By comparing the wear scars, it was also clear that all P-SiSO samples performed significantly better than the reference PFPE fluid in terms of wear, which was in line with our previous results using similar RTILs [24]. Although the additives appear to influence the wear scar morphology (as seen from the change in wear scar light reflection in Figure 7c), it was difficult to quantify the change in tribological performance in terms of wear with high accuracy.…”
Section: Stage 2: Effect Of Additives In P-sisosupporting
confidence: 59%
“…These tests used varying loads and temperatures in a manner similar to experiments in Reference [24], but with a focus on surface analysis as well as friction response. In the first test, V{100-300 N/25 • C/120 min}, the lubricant was evaluated by increasing the load in increments from 100 N to 300 N (corresponding to maximum Hertzian pressures of 2.1-3.0 GPa), at constant temperature, for a total test duration of 120 min.…”
Section: Ball-on-flat Reciprocating Tribotestmentioning
confidence: 99%
“…Overall, the friction results show that an increase in the P concentration for the AE (1 : 1) mixture was benecial in providing a sufficient load-carrying capacity to separate the rubbing parts while facilitating the reaction of the phosphonium phosphate IL with the metal surface. 54 As previously reported, when a metal surface is lubricated by IL, a layer structured lm is formed initially by physical adsorption. 55 The anions react rst with the positively charged metal surface to form a layer composed of iron phosphates.…”
Section: Tribo-evaluation Of Ionic Liquidsmentioning
confidence: 62%
“…Due to the presence of two hydroxyl groups at the terminal of its molecule, the friction modier could be adsorbed onto the metal surface thereby providing an extra wear protection. 54 The different frictional and wear behaviours of the evaluated mixtures could be related to the chemical composition of the formed tribolms which will be discussed within the next section.…”
Section: Tribo-evaluation Of Ionic Liquidsmentioning
confidence: 99%
“…Some of these features make them interesting as lubricants and ILs have begun to gain attention for their tribological properties since 2001 [4]. Several researchers have shown that ILs demonstrate low wear and friction in steel-steel contacts [4][5][6][7][8][9], aluminium-steel contacts [4,10,11], nickel-steel contacts [12], copper-steel contacts [4] and ceramic-steel contacts [4,13]. Aside from potential problems with corrosion and additive compatibility most ILs are significantly more expensive to manufacture compared to more common lubricants.…”
Section: Introductionmentioning
confidence: 99%